Combined effects of two mutations in von Willebrand disease 2M phenotype - Woods, Adriana Inés (2018)
Background: Type 2M von Willebrand disease (VWD2M) is usually characterized byVWF:RCo/VWF:Ag<0.6 and normal multimeric profile; desmopressin (DDAVP) challengetest commonly shows poor response of VWF:RCo.Objective: We describe the bleeding tendency and the laboratory phenotype in a patient carrying two heterozygous mutations affecting VWF-A1 domain and VWF-A2domain.Subjects/methods: A 12-year-old patient (O blood group) with severe hemorrhagictendency was phenotypically and genotypically analyzed; his parents were alsostudied.Results: The proband showed decrease FVIII:C, VWF:RCo/VWF:Ag, and VWF:CB6/VWF:Ag ratios, but normal platelet count, VWF:CB1/VWF:Ag ratio, VWFpp and multimeric pattern, suggesting a VWD2M phenotype. The DDAVP challenge test, compared to controls (VWD2M patients with mutations in VWF-A1 domain), showed lower increase of FVIII:C and VWF:Ag than in heterozygous, but very similar to homozygous control. Two mutations were found in heterozygous and trans presentation: p.Pro1648fs*45 and a novel missense mutation, p.Arg1426Cys. The mother was p.Arg1426Cys heterozygous carrier, with few clinical symptoms. The father was asymptomatic, with no mutations. The p.Pro1648fs*45 was considered an apparent de novo mutation; proband?s AS-PCR revealed mosaicism in the paternal allele. According to the predicted models, p.Arg1426Cys would not be affecting the binding of GPIbα to A1 domain, whereas p.Pro1648fs*45 seems to modify the folding of A2 domain, and in this way, it would affect the binding to GPIbα and type VI collagen. We believe that the combination of these two heterozygous mutations, in a child with O blood group, could result in a defective phenotype enhancer.eCollection 2018 Jan